(untitled) (Studia Prawnicze / The Legal Studies, 2023)
Autor artykułu przybliża czytelnikom problematykę kodyfikacji prawa cywilnego w Polskiej Rzeczypospolitej Ludowej. Przedstawione zostają wysiłki polskich prawników na rzecz ujednolicenia systemu prawnego w okresie przed i po II wojnie światowej. Zadaniem ówczesnego jak i współczesnego ustawodawcy była unifikacja przepisów obowiązujących na terenie Rzeczypospolitej. Autor opisuje działania legislacyjne na rzecz ujednolicenia przepisów prawa cywilnego zaraz po zakończeniu okupacji hitlerowskiej, współpracę z Czechosłowacją w dziedzinie prawa rodzinnego. Ponadto przedstawia także wpływ uchwalenia Konstytucji z 22 lipca 1952 r. na proces kodyfikacji prawa cywilnego PRL. The author of this article familiarises readers with the codification of civil law in the People’s Republic of Poland. The efforts of Polish lawyers to unify the legal system in the period before and after the Second World War are presented. The task of the then as well as the modern legislator was to unify the laws in force in the Republic of Poland. The author describes legislative efforts to unify civil law immediately after the end of the Nazi occupation, cooperation with Czechoslovakia in the field of family law. In addition, he also presents the impact of the enactment of the Constitution of 22 July 1952 on the codification process of the civil law of the People’s Republic of Poland.